2022
DOI: 10.1002/cpt.2682
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Fexofenadine, but Not Pseudoephedrine, Is Markedly Decreased by Green Tea Extract in Healthy Volunteers

Abstract: Green tea (GT) alters the disposition of a number of drugs, such as nadolol and lisinopril. However, it is unknown whether GT affects disposition of hydrophilic anti-allergic drugs. The purpose of this study was to investigate whether pharmacokinetics of fexofenadine and pseudoephedrine are affected by catechins, major GT components.A randomized, open, 2-phase crossover study was conducted in 10 healthy Japanese volunteers. After overnight fasting, subjects were simultaneously administered fexofenadine (60 mg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…As evidenced by clinical studies, the significant degree of variability in the pharmacokinetic parameters of EGCG might be explained by genetic variations in the genes encoding the drug transporters MRP2 and organic anion transporter SLC21A6 (OATP1B1). It is possible that this interindividual heterogeneity could account for the quantities of green tea polyphenols in human plasma or their potential to induce beneficial effects [ 364 ] and their potential to trigger pharmacokinetic interaction with other drugs [ 365 , 366 , 367 , 368 ].…”
Section: Egcg In Cancer Prevention and Therapy?mentioning
confidence: 99%
“…As evidenced by clinical studies, the significant degree of variability in the pharmacokinetic parameters of EGCG might be explained by genetic variations in the genes encoding the drug transporters MRP2 and organic anion transporter SLC21A6 (OATP1B1). It is possible that this interindividual heterogeneity could account for the quantities of green tea polyphenols in human plasma or their potential to induce beneficial effects [ 364 ] and their potential to trigger pharmacokinetic interaction with other drugs [ 365 , 366 , 367 , 368 ].…”
Section: Egcg In Cancer Prevention and Therapy?mentioning
confidence: 99%
“…Common mechanisms include induction or inhibition of drug metabolizing enzymes, particularly the cytochrome P450s (CYPs), and transporters. Regarding transporters, studies showed green tea to decrease systemic area under the plasma concentration versus time curve (AUC) to the minimally metabolized drugs digoxin, fexofenadine, lisinopril, and nadolol 8–12 . These observations were attributed to inhibition of an intestinal uptake transporter(s) by green tea.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding transporters, studies showed green tea to decrease systemic area under the plasma concentration versus time curve (AUC) to the minimally metabolized drugs digoxin, fexofenadine, lisinopril, and nadolol. 8 , 9 , 10 , 11 , 12 These observations were attributed to inhibition of an intestinal uptake transporter(s) by green tea. Pharmacokinetic green tea–drug interactions involving biochemical targets in the intestine in addition to the CYPs and transporters, such as UDP‐glucuronosyltransferases (UGTs), remain understudied.…”
Section: Introductionmentioning
confidence: 99%